PLASMA-ASSISTED EXTRACTION OF HERBAL TEA BY-PRODUCTS - Grbić, Jovana; Bogdanović, Mihajlo; Mladenović, Dragana; Lazović, Saša; Mojović, Ljiljana; Djukić-Vuković, Aleksandra (Journal on Processing and Energy in Agriculture, 2023)
Traditional extraction methods involve the utilization of polar solvents and/or high temperatures. Both are often energy and time-consuming and require additional purification steps. Because of that, the quality of obtained extracts is at risk. Non-thermal plasma-assisted extraction is a promising technique that could increase process sustainability while following the principles of hurdle technology. In this work, we investigated the impact of plasma treatment on water-based extraction of antioxidative compounds from herbal tea by-products. Stinging nettle, hoary willowherb, and St. John’s Wort extracts were treated with plasma at different time intervals. Obtained extracts were analyzed for antioxidative capacity and total phenolic content. Their potential use as a growth medium for Ligilactobacillus sp. was also examined. Hoary willowherb extracts showed the highest total phenolic content and antioxidative activity. While plasma treatment slightly lowered the antioxidative capacity of these extracts, it improved microbial growth. As opposed to hoary willowherb, stinging nettle extracts’ antioxidative capacity was not affected by the plasma treatment. These extracts were also more suitable for bacteria growth. When supplemented with 25% v/v MRS broth, stinging nettle extracts provided a similar growth rate to pure MRS broth ( 109 CFU/ml), showing its potential in microbial biomass production and food and feed supplementation.